Selective DNAM-1 expression on small peritoneal macrophages contributes to CD4+ T cell costimulation - 渋谷 彰; 渋谷 和子; Takenaka Eri; Van Vo Anh; Yamashita-Kanemaru Yumi; Shibuya Akira; Shibuya Kazuko (Scientific reports, 2018)
Mouse peritoneal macrophages consist of two subsets: large peritoneal macrophages (LPMs) and small peritoneal macrophages (SPMs), defined as CD11bhiF4/80hi and CD11b+F4/80lo cells, respectively. We reveal that SPMs, but not LPMs, have the ability to present antigens to naïve CD4+ T cells. Coculture of SPMs with naïve ovalbumin (OVA) specific CD4+ T cells (OT-II) in the presence of OVA peptide effectively induced CD4+ T cells priming. SPMs, but not LPMs, strongly express DNAM-1, an activating immunoreceptor. Although antigen uptake and processing were comparable between WT and DNAM-1-deficient SPMs, deficiency of DNAM-1 on SPMs or blockade of DNAM-1 and its ligand interaction impaired CD4+ T cells priming by SPMs. Furthermore, T and B cell responses in mediastinal lymph nodes of mice intraperitoneally immunized with trinitrophenyl (TNP)–OVA protein in Alum adjuvant were enhanced by intraperitoneally transferred wild-type, but not DNAM-1-deficient, SPMs. We propose that SPMs are functionally distinct from LPMs, and DNAM-1 plays a costimulatory role in antigen presentation by SPMs.